Are auditory steady-state responses a good tool prior to pediatric cochlear implantation?. Issue 8 (August 2015) - Beck, Roberto Miquelino de Oliveira; Grasel, Signe Schuster; Ramos, Henrique Faria; Almeida, Edigar Rezende de; Tsuji, Robinson Koji; Bento, Ricardo Ferreira; Brito, Rubens de
Abstract Introduction ASSR allow frequency-specific evaluation in intensities up to 120 dB HL and detection of residual hearing in patients with severe-to-profound hearing loss. Aim to compare ASSR thresholds and behavioral test results in children with suspected severe-to-profound hearing loss. Methods Cross sectional study to compare ASSR and behavioral responses (VRA or audiometry) in 63 pediatric cochlear implant candidates (126 ears) aged between 6 and 72 months. We included children with normal otomicroscopy, absent responses to click-ABR and otoaccoustic emissions. We excluded children with inner ear malformations, auditory neuropathy spectrum disorder or who did not complete VRA or achieve EEG noise < 30 nV during the ASSR test. Air-conduction ASSR stimuli were continuous sinusoidal tones presented at 0.5, 1, 2 and 4 kHz starting at 110 dB HL. Behavioral thresholds were acquired with warble tones presented at 0.5, 1, 2 and 4 kHz in each ear through insert or head phones at maximum presentation level of 120 dB HL. Results Behavioral thresholds were obtained in 36.7% (185/504) of all frequencies in all subjects, 9% in intensities >110 dB HL. Among 504 ASSR measurements, 53 thresholds were obtained (10.5%). Overall 89.5% of the tested frequencies did not show any response at 110 dB HL. Most responses were at 500 Hz. Mean differences between behavioral and ASSR thresholds varied from 0.09 to 8.94 dB. Twenty-seven comparisons of behavioral and ASSR thresholds were obtained: 12 at 0.5 kHz, 9 at 1 kHz, 5 at 2 kHz and 1 at 4 kHz. Absent responses were observed in both tests in 38.1% at 0.5 kHz, 52.4% at 1 kHz, 74.6% at 2 kHz and 81.0% at 4 kHz. Specificity was > 90% at 1, 2 and 4 kHz. In ears with no behavioral response at 120 dB HL all ASSR thresholds were in the profound hearing loss range, 90% of them were ≥110 dB HL. Conclusion Among 63 pediatric CI candidates, absent responses to high-intensity ASSR was the major finding (specificity > 90%) predicting behavioral thresholds in the profound hearing loss range. These findings can be helpful to confirm the decision for cochlear implantation.